Mindset the new psychology of success - Dweck, Carol S. 1946- (Ballantine Books, 2016)
In the course of over twenty years of research, leading motivation and personality psychology expert Carol Dweck has discovered that our mindset is not a minor personality quirk, it actually creates our whole mental world, and explains how we become optimistic or pessimistic. Mindsets shape goals, attitudes toward work and relationships, and how we raise our kids, ultimately predicting whether or not we will fulfill our potential. Dweck has found that people have of two basic mindsets: fixed, or growth. Those with fixed mindsets believe that their talents and abilities are set in stone and are unchangeable, and that they must prove themselves over and over, trying to look smart and talented at all costs. Those with a growth mindset, however, know that talents can be developed and that great abilities are built over time. This is the path of opportunity ; and success. Dweck reveals how creative geniuses in all fields ; music, literature, science, sports, business ; apply the growth mindset to achieve results. Perhaps even more important, she shows us how we can change our mindset at any stage of life to achieve true success and fulfillment. She looks across a broad range of applications to help parents, teachers, coaches, and executives see how they can promote a growth mindset.